2006
DOI: 10.1017/s1740925x06000251
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes regulate formation of nodes of Ranvier via the recognition molecule OMgp

Abstract: The molecular mechanisms underlying the involvement of oligodendrocytes in formation of the nodes of Ranvier (NORs) remain poorly understood. Here we show that oligodendrocyte-myelin glycoprotein (OMgp) aggregates specifically at NORs. Nodal location of OMgp does not occur along demyelinated axons of either Shiverer or proteolipid protein (PLP) transgenic mice. Over-expression of OMgp in OLN-93 cells facilitates process outgrowth. In transgenic mice in which expression of OMgp is down-regulated, myelin thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 49 publications
4
33
2
Order By: Relevance
“…Notably, netrin-1 labeling was selectively enriched in perinodal regions, based on localization with the perinodal marker Caspr. Perinodal localization has been observed previously also with the myelinassociated inhibitors OMgp and MAG (Huang et al, 2005;Nie et al, 2006). Netrin-1 expression persisted 3 months after spinal cord injury (Fig.…”
Section: Netrin-1 Is Expressed By Mature Oligodendrocytes In the Adulsupporting
confidence: 76%
See 1 more Smart Citation
“…Notably, netrin-1 labeling was selectively enriched in perinodal regions, based on localization with the perinodal marker Caspr. Perinodal localization has been observed previously also with the myelinassociated inhibitors OMgp and MAG (Huang et al, 2005;Nie et al, 2006). Netrin-1 expression persisted 3 months after spinal cord injury (Fig.…”
Section: Netrin-1 Is Expressed By Mature Oligodendrocytes In the Adulsupporting
confidence: 76%
“…Both netrin-1 and its receptors are expressed in the intact and lesioned adult CNS. Netrin-1 is expressed by oligodendrocytes, and is enriched in proximity to paranodal loops at nodes of Ranvier in adult white matter, in a location similar to that described for two other myelin-associated inhibitors, OMgp and MAG (Huang et al, 2005;Nie et al, 2006). The repulsion-mediating class of netrin UNC5 receptors is expressed by rubrospinal and corticospinal motor neurons, and by neurons in all laminas of spinal cord gray matter.…”
Section: Discussionmentioning
confidence: 61%
“…However, recent studies have reported NogoA involvement in cell migration and axonal fasciculation during brain development (Mingorance et al, 2004;Mingorance-Le Meur et al, 2007). The same happens with other MAIs such us Omgp with key roles in the formation of nodes of Ranvier (Nie et al, 2006).…”
Section: Introductionmentioning
confidence: 79%
“…This could either indicate a redundant role that can be compensated upon Lingo-1 or NgR1 loss by other gene products or its implication in cell processes not analyzed to date. For example, the participation of Nogo-A or Omgp in functions different from those associated to axonal regeneration has been recently revealed (Nie et al, 2006;Voeltz et al, 2006;Mingorance-Le Meur et al, 2007). As indicated, further studies will be required to ascertain these possibilities.…”
Section: Lingo-1 Protein Is Present In Neurons and In Immature Oligodmentioning
confidence: 99%
“…52 The ordered arrangement of ion channels at the nodes of Ranvier (and therefore conductive properties of axons) also critically depends on correct myelination. 53 Oligodendrocytes are considered to be essential to long-term axonal integrity, potentially through trophic support mechanisms and axon−glia metabolic coupling mechanisms 54,55 leading to a widely held view that axon− myelin interactions have an important neuroprotective role (and by extension impact disease progression when perturbed). 16 Consequently, CS-induced delays in myelination are of significant clinical importance when considering treatment of a range of pediatric and adult pathologies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%